2015
DOI: 10.1128/aem.03721-14
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Independent Genetic Events Disrupt the Secondary Metabolism Gene perA in Certain Symbiotic Epichloë Species

Abstract: Peramine is an insect-feeding deterrent produced by Epichloë species in symbiotic association with C 3 grasses. The perA gene responsible for peramine synthesis encodes a two-module nonribosomal peptide synthetase. Alleles of perA are found in most Epichloë species; however, peramine is not produced by many perA-containing Epichloë isolates. The genetic basis of these peramine-negative chemotypes is often unknown. Using PCR and DNA sequencing, we analyzed the perA genes from 72 Epichloë isolates and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 44 publications
2
36
1
Order By: Relevance
“…Degenerate PCR primers were designed using perA sequences from Epichloë spp. that were known to encode functional peramine synthetases (Berry et al, 2015b;Schardl et al, 2013) and the MR_perA sequence obtained from the M. rileyi RCEF 4871 genome . Primers were designed to highly conserved perA target regions, incorporating the minimum number of degenerate base codes necessary to achieve reliable amplification from all aligned sequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Degenerate PCR primers were designed using perA sequences from Epichloë spp. that were known to encode functional peramine synthetases (Berry et al, 2015b;Schardl et al, 2013) and the MR_perA sequence obtained from the M. rileyi RCEF 4871 genome . Primers were designed to highly conserved perA target regions, incorporating the minimum number of degenerate base codes necessary to achieve reliable amplification from all aligned sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The known distribution of perA was previously limited to Epichloë spp., though the presence of a perA pseudogene in the closely related species Periglandula ipomoeae suggested that the evolutionary origins of perA extend back to at least the common ancestor of these genera (Berry et al ., ; Schardl et al ., ). Our results demonstrate that MR_perA encodes a functional peramine synthetase, establishing a precedent for distribution of perA orthologs beyond genus Epichloë .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lolii (LpTG-1; Lolium perenne taxonomic group) and LpTG-2 possess intact perA genes, while non-peramineproducing strains (belonging to LpTG-3 and LpTG-4) are characterised by partial deletions and premature stop codons (Hettiarachchige et al 2015). The complete perA gene encodes two adenylation (A1 and A2) domains, two thiolation (T1 and T2) domains, a methylation (M) domain, a condensation (C) domain, and a reductase (R) domain, which may be sufficient to produce peramine (Schardl et al 2013b;Berry et al 2015). Several variants of perA with variability of the number of functional domains have been identified in different Epichloë species.…”
Section: Introductionmentioning
confidence: 99%
“…Several variants of perA with variability of the number of functional domains have been identified in different Epichloë species. Expression of a perA variant which lacks the reductase domain may produce a metabolite related to peramine (Schardl et al 2013b;Berry et al 2015).…”
Section: Introductionmentioning
confidence: 99%